A Preliminary Study on Infrared Thermograph of Metabolic Syndrome - Gao, Meng-jiao; Xue, Hui-zhong; Cai, Rui; Jiang, Bi-yao; Mi, Bao-hong; Chen, Zong-jun; Shi, Yin-chun; Xiao, Yong-hua; Zhang, Wen-zheng (Frontiers in Endocrinology, 2022)
Objective: To explore the temperature distribution characteristics of the face, palms, feet and the trunk area of metabolic syndrome (MS) through infrared thermography (IRT) and provide evidence for the application of IRT in the assistant evaluation of MS population. Methods: We collected thermographs of 184 participants (91 males, 93 females) and further divided participants of each gender into 4 groups according to the number of abnormal metabolic indexes. Mean temperatures of 6 Region of Interests (ROIs) (face, anterior trunk, bilateral palms and dorsum of feet) were calculated. Comparisons of the mean temperatures between genders, among groups and ROIs were carried out. Results: Male participants had higher mean temperature in their face, palms (P<0.01) and dorsum of feet (P<0.05), and lower mean temperature in the anterior trunk (P<0.01). Female participants with MS had higher mean temperature in their palms and dorsum of feet (P<0.01) and lower mean temperature in the anterior trunk (P<0.01) than normal participants. Similar tendencies were shown in the mean temperature of the left palms and trunk of MS males. With the increase of the number of abnormal metabolic indexes, it seems that the mean temperature gradually increased in palms and dorsum of feet, and decreased in the anterior trunk. Conclusion: The thermograph of MS exhibits certain characteristics. This may help reveal the correlations between Infrared thermography and metabolic disorders.